“It’s only when somebody says a tool worked for them that I believe it will work for me”: Socio-tecture as a lens for digital transformation - Awori, Kagonya; Allela, Melisa Achoko; Nyairo, Stephanie; Maina, Samuel Chege; O'Neill, Jacki (2022 Conference on Computer Supported Cooperative Work, 2022)
Small and Medium sized Businesses (SMBs) make up majority of employment in Africa (around 80%). Understanding the digital transformation that SMBs in Africa went through during the pandemic can play an important role in uncovering how to build solutions that better support the African business and African worker. In this paper we report on findings from a qualitative study with 40 SMBs in Kenya. The study aimed to understand the lived experience of digital transformation, the impacts of COVID-19 on their businesses, and how they responded to such impacts using technology. We found that COVID-prompted digital transformation was reactive and opportunistic, plus social and collective. Moreover, the socialness of business goes way beyond digital transformation, and influences how SMBs in Kenya start, develop and are sustained. In illustrating this, we offer a lens to understanding work and workers of SMBs in Kenya and similar contexts across the globe.